Minute Colon Perforation by a Nonabsorbable Suture Knot after Uterine Myomectomy - Hyeonkyeong Kim; Jinhoon Nam; Ryung-Ah Lee (The Ewha Medical Journal)
We report a rare case of suture material-related colon perforation. A 60-year-old woman visited clinics because of the nonspecific abdominal discomfort for several months. There were no specific medical history except previous laparoscopic myomectomy 15 years ago. Colonoscopy and abdomen-pelvis computed tomography revealed an unknown foreign body penetrating the sigmoid colon wall adjacent to the uterus. We performed laparoscopic exploration with foreign body removal and primary colon wall repair. The foreign body was identified as a non-absorbable suture material suggestive of used in previous myomectomy. With recent trends for minimally invasive procedures in the field of pelvic organ surgery, surgeons, especially those without sufficient training have to pay attention to selecting the proper surgical suture materials. (Ewha Med J 2022;45(3):e7)